ANALYSIS OF ADIDAS SHOE QUALITY CONTROL CELL 1 FACTORY 3 IN THE ASSEMBLING PROCESS USING SEVENTOOLS AND FMEA METHODS - Nisa Firdausi Riski; Gunawan Mohammad; Budi Lofian (Science and Technology (SciTech), 2024)
PT Parkland World Indonesia Jepara is a shoe manufacture producing one of type of Adidas’ shoes model which is Runfalcon 5W. The shoe production process in the assembling process has many defects in both of the upper and bottom components. It necessary to conduct quality control analyse of defects using seven tools’ method as a quality control tools that can be used in the process of quality control, and then using FMEA (Failure Mode and Effect Analysis) to improve the reliability and safety of a process by identifying potential failure modes, failure effects, causes of failure, detection mode and determining scores on severity, occurence, and detection for the Risk Priority Number (RPN) in assembling process. Based on result of the seven tools method analysis, the highest type of shoe’s defect in Runfalcon 5W is dirty or glue stains as many as 192 pairs, midsole to upper as many as 138 pairs, and over cementing as many as 105 pairs, and meanwhile based on result of RPN assessment on midsole to upper with a score 224, dirty or glue stain with a score 126, and over cementing with a score 72. Proposed improvement for dirty defects or glue stains by performing periodic hyginie maintenance and doing work according to procedures, midsole to upper defects by checking the quality of the outsole and engine settings periodically, over cementing defects by performing technical presses according to work procedures. By implementing this proposal, it is hoped that it can reduce the level of defects in the Adidas Runfalcon 5W shoe assembling process.